2016
DOI: 10.5562/cca2915
|View full text |Cite
|
Sign up to set email alerts
|

Towards Reassignment of the Methionine Codon AUG to Two Different Noncanonical Amino Acids in Bacterial Translation

Abstract: Genetic encoding of noncanonical amino acids (ncAAs) through sense codon reassignment is an efficient tool for expanding the chemical functionality of proteins. Incorporation of multiple ncAAs, however, is particularly challenging. This work describes the first attempts to reassign the sense methionine (Met) codon AUG to two different ncAAs in bacterial protein translation. Escherichia coli methionyl-tRNA synthetase (MetRS) charges two tRNAs with Met: tRNA fMet initiates protein synthesis (starting AUG codon),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 75 publications
1
11
0
Order By: Relevance
“…In addition to the host metabolic engineering strategies described above, these issues could be further addressed by improving the performance of endogenous MetRS using directed evolution of its substrate specificity. This can also be done with imported heterologous MetRS enzymes from other phylogenetically distant sources as previously described [6]. Next, further optimisation of the fermentation protocol could be accomplished by, for example, by switching to recombinant expression in batch cultures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the host metabolic engineering strategies described above, these issues could be further addressed by improving the performance of endogenous MetRS using directed evolution of its substrate specificity. This can also be done with imported heterologous MetRS enzymes from other phylogenetically distant sources as previously described [6]. Next, further optimisation of the fermentation protocol could be accomplished by, for example, by switching to recombinant expression in batch cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Met contains a unique thioether unit, whose sulphur atom (although often involved in S/π interactions with adjacent aromatic amino acids) can easily be replaced by methylene [3], oxygen [2], selenium [4] and even tellurium [5]. Many non-canonical isosteric analogues and surrogates of Met, which are translationally active, are activated by methionyl-tRNA synthetase (MetRS) with a kinetic turnover similar to those of the native substrate [6]. For this reason, the plasticity of substrate binding in wild-type MetRS can be used to co-translate a relatively large number of analogues and surrogates such as metoxinine [2], ethionine [7], homopropargylglycine [8] and azidohomoalanine [9].…”
Section: Introductionmentioning
confidence: 99%
“…Expressing this mutant E. coli MetRS in HEK293T afforded specific incorporation of Anl at the initiating position and Met at internal AUG positions . A similar strategy was used in E. coli employing what was thought to be an orthogonal MetRS from Sulfolobus acidocaldarius ( Sa ‐MetRS) with unique ncAA recognition . It was hypothesized that deleting elongator tRNA Met from the E. coli genome with rescue by Sa ‐MetRS/ Sa ‐tRNA Met would allow for specific incorporation of ethionine ( 43 , Eth) at elongator AUG codons facilitated by Sa ‐MetRS/ Sa ‐tRNA Met while incorporation of azidohomoalanine ( 54 , Aha) could be restricted to the initiator position, incorporated by endogenous MetRS/tRNA fMet .…”
Section: Initiation With Noncanonical Amino Acids In Vivomentioning
confidence: 99%
“…However, this strategy was met with limited success as it was found that the E. coli and S. acidocaldarius MetRS enzymes were not completely orthogonal. To overcome this problem, it was proposed that a demonstrated orthogonal aaRS/tRNA pair, such as the pyrrolysyl‐tRNA synthetase (PylRS)/tRNA Pyl could be evolved for Met recognition and used to replace elongator tRNA Met . Regardless of the method used to improve site‐selectivity, RSI will still cause global integration of the amino acid analogue into the host proteome.…”
Section: Initiation With Noncanonical Amino Acids In Vivomentioning
confidence: 99%
“…leads to a genetic firewall . In cases when CMOs are not able to create the essential synthetic nutrient (trophic containment) , combination of the genetic firewall with this “alien ersatz” increases the degree of biocontainment . The likelihood of spreading genetic material from genetically modified organisms (GMOs) into the environment is still underestimated and not well studied .…”
Section: Introduction To Xenobiologymentioning
confidence: 99%